Response of Variety and population density on yield attributes and yield of boro rice(Oryza sativa) - Mausam, S.M.; Ali, M.H.; Hasanuzzaman, M.; Chowdhury, I.F.; Mandal, M.S.H.; Jerin, R. (Annals of Agricultural Research, 2014)
The present study was conducted at the Agronomy Field, Sher-e- Bangla Agricultural University(SAU), during boro season(November 2010 to April 2011) to investigate the influence of population density on growth and yield of inbred and hybrid boro rice. The treatment consisted of four varieties viz. BRRI Dhan28, BRRI Dhan 29, BRRI Dhan 2, BRRI Hybrid Dhan 2 and ACI Hybrid DHAN 2 and four population density Â viz. 1,2,3,4 seedling hill-1. The experiment was laid out in randomized complete block design with three replications. The effect of variety, population density hill-1 and their interaction showed significant variation in respect of yield contributing parameters and yield. ACL Hybrid Dhan 2, 2seedling hill-1 and their combination increased yield attributing parameters, grain and straw yield for boro season. Â